Mt. Hamilton Juvenile Grange display - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a display of arts and crafts. Above the display a sign reads: "Mt. Hamilton Juvenile, Santa Clara Co." A sign at the bottom of the display reads: "Mt. Hamilton Juvenile Grange no. 36."